Event Management System for Webinars and Survey - Ismail; Syafrinal; Abdus Salam; Rahmi Hajriyanti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2022)
Webinars and surveys have been widely used. Popular applications such as ezTalks, Zoom, Demio, Google Meet, LiveStorm have been used in seminars and online meetings. For every webinar activity, the organizers often carry out survey activities to see feedback from participants, google forms applications, survey monkeys, typeforms, zoho surveys, and gizmo surveys are used to see responses from all participants. In addition, several organizers also gave appreciation in the form of certificates. However, the management of many webinars is often an obstacle to seeing the results of each activity and the participants who take part in the activity. Although the use of google forms has been very good and effective, the lack of features in the management of webinar activities is a problem in itself in making reports in a short time. Therefore, we need a service application that can assist in the management of webinar activities and has survey features from registration, attendance to certificates. Where later application users (organizations, committees) can fill out webinar activities and can propose surveys for each activity carried out. In software development, Agile Development Methods (ASD) are used, Event Management System for Webinars and Survey applications that the researchers built using CodeIgniter and React-Js. In the test, we plan the data analysis to be divided into three parts, namely Demographic Analysis Results, Reliability Test Results Analysis, Validity, and Data Processing Analysis. Analysis Data processing includes Importance-Performance Analysis (IPA). So far, webinar and survey management applications have completely fulfilled needs such as making a number of questions in the form of multimedia and sharing research data, but webinar management applications with survey services in an application have not been carried out. It is hoped that the development of research on webinar and survey management applications will produce more visualitative applications and be able to manage webinar activities and reporting related to surveys, reporting participants for each activity carried out. Based on the results of the Importance Performance Analysis, it is known that the average value of the level of expectation or importance for usability is 3.97, and the average value for the level of performance is 3.68. the average value of the level of expectation or importance for information quality is 4.07, and the average value for the level of performance is 3.70. the average value of the level of expectation or importance for service interaction is 3.94, and the average value for the level of performance is 3.71.